Impact of generalized Fourier's law and Fick's law for MHD flow of Ag‒H2O and TiO2‒H2O nanomaterials. Issue 6 (4th November 2019) - Gupta, Sumit; Kumar, Devendra; Singh, Jagdev; Gupta, Sandeep
Abstract : Purpose: The purpose of this paper is to investigate the effect of inclined magnetic field, variable viscosity and Cattaneo–Christov heat and mass flux theories on the steady MHD free convective boundary layer flow of viscous, incompressible and electrically conducting water-driven silver and titanium-oxide nanofluids over a vertical stretching sheet. Design/methodology/approach: The boundary layer equations of momentum, energy and nanoparticle concentration are partial differential equations in nature, which are reduced to nonlinear ordinary differential equations by means of similarity transformations. The resulting nonlinear equations are solved analytically by means of optimal homotopy analysis method. Findings: Assessments with numerical results are performed and are found to be in an excellent agreement. Numerical results of the skin friction factor, the local Nusselt number and the local Sherwood number are obtained through tables. The effects of various physical parameters on the velocity, temperature and nanoparticles fraction are incorporated through graphs. The study analyzes the efficiency of heat transfer of nanofluids in cooling plants and rubber sheets. Originality/value: No research works have been conducted to evaluate the effects of various physical phenomena on the copper and titanium nanofluids flow.